Introducing Energy-efficient Clean Technologies in the Brick Sector of Bangladesh - World Bank (World Bank, 2012)
This study's objectives are: (i) to present the pros and cons of existing and alternative brick technologies in Bangladesh with specific focus on pollution and energy efficiency; (ii) to estimate the private and social benefits of these technologies (iii) to summarize China's experience in the development of the brick industry, as the world leader brick producer and (iv) to provide concrete recommendations for adopting cleaner technologies in Bangladesh. The study focuses on the brick cluster located in northern Dhaka, which comprises 530 Fixed Chimney Kiln (FCKs) that produce 2.1 billion bricks annually (14 percent of the country's brick production). As the brick sector is a prominent contributor to air pollution in Dhaka, it is important to distinguish its contribution to the city's air pollution from other sources, including transport and other industries. Because of limited data availability, the analysis relies on the most realistic assumptions drawn from monitored data in Bangladesh or neighboring countries (i.e., Nepal and India). As a result, the estimated net returns for each technology are orders of magnitude rather than precise estimates. This report analysis the brick sector in Bangladesh and assesses the feasibility of cleaner alternative technologies.